Antimony(III/V) removal from industrial wastewaters treatment of spent catalysts formally used in the SOHIO acrylonitrile process - Foster, Richard I (Water science and technology : a journal of the International Association on Water Pollution Research, 2019)
A treatment and volume reduction process for a spent uranium-antimony catalyst has been developed. Targeted removal, immobilization and disposal of the uranium component has been confirmed, thus eliminating the radiological hazard. However, significant concentrations of antimony ([Sb] ≥ 25-50 mg L-1) remain in effluent from the process, which require removal in compliance with Korean wastewater regulations. Antimony(III/V) removal via co-precipitation with iron has been considered with optimal pH, dose and kinetics being determined. The effect of selected anions - Cl-, SO42- and PO43- - have also been considered, the latter present due to a prior uranium removal step. Removal of Sb(III) from both Cl- and SO42- media and Sb(V) removal from Cl- media to below release limits were found to be effective within 5 minutes at an iron dose of 8 mM (molar ratio, [FeIII]/[Sb] = 20) and a target pH of 5.0. However, Sb(V) removal from SO42- was significantly hampered requiring significantly higher iron dosages for the same removal performance. Phosphate poses significant challenges for the removal of Sb(V) due to competition between PO43- and Sb(OH)6- species for surface binding sites, attributed to similarities in chemistries and a shared preference for an inner vs outer binding mechanism